Microstructure properties of welded S420MC dual phase steel - Çalık, Adnan; Uçar, Nazım (International Journal of Computational and Experimental Science and Engineering, 2024)
In this study, the weldability and microstructure properties of S420MC dual phase (DP) steel joints fabricated by the resistance spot welding method (RSW) were investigated. The microstructures of the welds were examined by SEM and optical microscopy. The results showed that the microstructure of the weld metal region completely transformed into the ferrite phase, and deep and wide cracks occurred in this region and heat-affected zone. It was concluded that the RSW method should not be recommended for welding DP steel.